Stone yard devotional [large type] - Wood, Charlotte, 1965- (Random House Large Print, 2025)
Burnt out and in need of retreat, a middle-aged woman leaves Sydney to return to the place she grew up, taking refuge in a small religious community hidden away on the stark plains of rural Australia. She doesn't believe in God, or know what prayer is, and finds herself living this strange, reclusive existence almost by accident. But disquiet interrupts this secluded life with three visitations. First comes a terrible mouse plague, each day signaling a new battle against the rising infestation. Second is the return of the skeletal remains of a sister who disappeared decades before, presumed murdered. And finally, a troubling visitor plunges the narrator further back into her past.--